Long‐term efficacy of fibrin glue injection for perianal fistulas in patients with Crohn's disease. (29th December 2020) - Vidon, Mathias; Munoz‐Bongrand, Nicolas; Lambert, Jérôme; Maggiori, Léon; Zeitoun, Jean‐David; Corte, Hélène; Panis, Yves; Seksik, Philippe; Treton, Xavier; Abramowitz, Laurent; Allez, Matthieu; Gornet, Jean‐Marc
Abstract: Aim: The treatment of perianal fistulas in Crohn's disease remains challenging. Fibrin glue injection has previously shown short‐term efficacy in a randomized controlled trial. No long‐term data are available to assess the benefit of this treatment. Methods: This retrospective multicentre study included all patients with drained fistulas treated by at least one fibrin glue injection between January 2004 and June 2015 in three tertiary French centres. The primary end‐point was the rate of complete clinical remission at 1 year after injection defined by the closure of all fistula tracts with no need for iterative anal surgery or for optimization of immunosuppressants and/or biologics. Results: In all, 119 patients (median age 33 years, complex fistulas 65%, median previous anal surgery two, median Harvey Bradshaw score 3, immunosuppressants exposure 50%, anti‐tumor necrosis factor exposure 60% with median time of administration of 1.1 year) were analysed with a median follow‐up of 18.3 months. The complete clinical remission rate at 1 year was 45.4%. The primary end‐point was achieved in 63% of the cases in the combination therapy group and 37% in other patients. The only predictor of complete clinical remission at 1 year was combination therapy at the time of injection ( P = 0.01). The rate of early reintervention after glue injection was 2.5%. The cumulative incidence of iterative anal surgery and ostomy in the whole population was 54% and 5.6% respectively at 5 years. Conclusion: An adjunct of fibrin glue to conventional medical therapy may be an effective and safe treatment for perianal fistulas in patients with Crohn's disease.